Effects of blocking on defense performance in beach handball - Nicklas, A.; Middell, O.; Fasold, F.; Klatt, S. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
This study investigated if blocking is a crucial factor of success in beachhandball. To this end, a video analysis of the Men's European Beachhandball Championship 2017 was conducted. Blocking improved the defense success rate for all shots, spin shots, specialist throws, and goalkeeper throws, while the absence reduced the defense success rate for all shots, spin shots, inflight throws, and one point throws. Thus, blocking could be an important factor for success.